Fluctuation in the number, type and activity of blood neutrophils in cows exhibiting successful and unsuccessful completion of gestation cycle. Issue 6 (2nd November 2017) - Mohammed, Seid; Aarti, Kamboj; Kalyan, Ankita; Alhussien, Mohanned Naif; Manjari, P.; Yadav, Munna lal; Sheikh, Aasif Ahmad; De, Sachinandan; Mohanty, A. K.; Dang, Ajay Kumar
Abstract: Neutrophils (first line of cellular defense) are capable of detecting presence of foreign genome in the mother's womb. Role of neutrophils during full gestation cycle of ruminants and the difference in their number, type, and activity in successful and unsuccessful pregnancies is not known. To evaluate this, blood samples were collected at artificial insemination (0 day) and on days 10, 14, 16, 18, and 21 in non-pregnant (NP) cows. However in pregnant (P) cows, samples were collected as indicated above and every 30 days for the complete gestation. In aborted cows, samples were collected as above till abortion. Higher total leukocyte counts were observed in NP and aborted cows at abortion. Neutrophil: lymphocyte ratio increased significantly ( p  < 0.05) in NP and aborted cows. Phagocytic activity (PA) and myeloperoxidase concentrations were significantly higher ( p  < 0.05) on day 18 post insemination in NP cows. PA and myeloperoxidase also increased significantly ( p  < 0.05) at abortion in aborted cows. Neutrophils exhibited limited decrease in their number and activity in successful pregnancies during implantation. After that their number and activity were constantly maintained throughout the gestation cycle. Any increase in the number and inflammatory activity of neutrophils may lead to non-pregnancy or loss in pregnancy.